Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction